2020
DOI: 10.3390/medicina56060289
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Support in Coronavirus 2019 Disease

Abstract: The epidemic that broke out in Chinese Wuhan at the beginning of 2020 presented how important the rapid diagnosis of malnutrition (elevating during intensive care unit stay) and the immediate implementation of caloric and protein-balanced nutrition care are. According to specialists from the Chinese Medical Association for Parenteral and Enteral Nutrition (CSPEN), these activities are crucial for both the therapy success and reduction of mortality rates. The Chinese have published their recommendations includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 42 publications
0
79
0
13
Order By: Relevance
“…The regular intake of vitamin A has been reported to decrease the infectivity and seriousness of many diseases, such as diarrhea, pneumonia, measles, malaria, and AIDS [ 65 ]. Vitamin A deficiency decreases bovine coronavirus vaccines’ efficiency and makes the animals more susceptible to infections [ 66 , 67 ]. It has been reported that the infectious bronchitis virus (IBV) infections caused by a strain similar to CoVs were more common in vitamin-A-deficient chickens than in those given vitamin A supplements [ 68 ].…”
Section: Vitamins and Immune Systemmentioning
confidence: 99%
“…The regular intake of vitamin A has been reported to decrease the infectivity and seriousness of many diseases, such as diarrhea, pneumonia, measles, malaria, and AIDS [ 65 ]. Vitamin A deficiency decreases bovine coronavirus vaccines’ efficiency and makes the animals more susceptible to infections [ 66 , 67 ]. It has been reported that the infectious bronchitis virus (IBV) infections caused by a strain similar to CoVs were more common in vitamin-A-deficient chickens than in those given vitamin A supplements [ 68 ].…”
Section: Vitamins and Immune Systemmentioning
confidence: 99%
“…18,25,26 Although feeding the critically ill patient and taking into consideration vasoactive medications and propofol infusion is common practice for the critical care RDN, challenges arise because EN may be delayed, owing to the high requirement and lengthy time frame of use of vasoactive medications in this patient population. 27 Executing early nutrition should always be aimed for, and COVID-19 with circulatory shock should not be considered as a contraindication to EN unless there is an accompanying enteral feed intolerance. 28 Prokinetic agents are recommended in such cases to increase the gut motility and improve EN tolerability.…”
Section: Covid-19 In Icu and The 4 P's: Pressor Propofol Paralyticsmentioning
confidence: 99%
“…Bolus feeding, however, is neither recommended nor feasible in COVID-19 patients, according to the ASPEN guidelines. 27,45 Protein is one of the most important macronutrients to meet the nutrition need of critically ill patients (both COVID-19 and non-COVID-19). At our center, we frequently used modular for our patients (with a composition of 15 g per 30 mL protein modular).…”
Section: Strategies For Nutrition Support Allocation During the Covidmentioning
confidence: 99%
“…The European Society for Clinical Nutrition and Metabolism (ESPEN) and other authors proposed general nutritional recommendations for all stages of COVID-19 (25,26,82) . management of patients with COVID-19, whether for adults with polymorbidity or those in the ICU setting, which are independent factors associated with malnutrition and negative outcomes (82) .…”
Section: Prevention and Treatment Of Covid-19 Cachectic Patients Thromentioning
confidence: 99%